Photodynamic Inactivation of Human Herpes Virus In Vitro with Ga(III) and Zn(II) Phthalocyanines - Neli Vilhelmova-Ilieva; Vanya Mantareva; Diana Braikova; Ivan Iliev (Viruses)
Photodynamic inactivation (PDI) has been revealed as a valuable approach against viral infections because of the fast therapeutic effect and low possibility of resistance development. The photodynamic inhibition of the infectivity of human herpes simplex virus type 1 (HSV-1) strain Victoria at different stages of its reproduction was studied. PDI activity was determined on extracellular virions, on the stage of their adsorption to the Madin-Darby bovine kidney (MDBK) cell line and inhibition of the viral replication stage by application of two tetra-methylpyridiloxy substituted gallium and zinc phthalocyanines (ZnPcMe and GaPcMe) upon 660 nm light exposure with a light-emitting diode (LED 660 nm). The PDI effect was evaluated on extracellular virions and virus adsorption by the terminal dilution method and the change in viral infectivity, which was compared to the untreated control group. The decrease in viral titer (Δlgs) was determined. The effect on the replicative cycle of the virus was determined using the cytopathic effect inhibition (CPE) assay. The direct influence on the virions showed a remarkable effect with a decrease in the viral titer more than 4 (Δlg > 4). The influence of the virus to the cell on the stage of adsorption was also significantly affected by the exposure time and the concentration of applied photosensitizers. A distinct inhibition was evaluated for ZnPcMe at the viral replication stage, which demonstrated a high photoinactivation index (PII = 33.0). This study suggested the high efficacy of PDI with phthalocyanines on HSV-1 virus, with full inhibition caused by the mechanism of singlet oxygen generation. These promising data are a good basis for further investigations on the PDI application against pathogenic viruses.